2017
DOI: 10.3892/etm.2017.4561
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted whole-body magnetic resonance imaging with background body signal suppression/T2 image fusion for the diagnosis of acute cholecystitis

Abstract: Abstract. Prompt and accurate diagnosis is critical in the treatment of acute cholecystitis. Diffusion-weighted whole-body magnetic resonance imaging with background body signal suppression/T2 image fusion (DWIBS/T2) identifies areas with high signal intensity, corresponding to inflammation. In the present study, the records and images of patients with acute cholecystitis who underwent DWIBS/T2 between January 2013 and March 2014 were retrospectively analyzed. A total of 11 patients with acute cholecystitis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Although all factors that can cause an imbalance in the ratio of cholesterol to bile acid phospholipids or bile stasis are considered to be inducers of gallstone formation, the mechanism of gallstone formation is not yet fully understood. It is noteworthy that the vast majority of gallstone formations are accompanied by gallbladder inflammation [15]. On the contrary, gallbladder stones and gallbladder inflammation diseases are common diseases associated with gallbladder motility disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Although all factors that can cause an imbalance in the ratio of cholesterol to bile acid phospholipids or bile stasis are considered to be inducers of gallstone formation, the mechanism of gallstone formation is not yet fully understood. It is noteworthy that the vast majority of gallstone formations are accompanied by gallbladder inflammation [15]. On the contrary, gallbladder stones and gallbladder inflammation diseases are common diseases associated with gallbladder motility disorders.…”
Section: Discussionmentioning
confidence: 99%
“…DWIBS is noninvasive, avoids radiation exposure, and allows imaging even in patients with poor renal function. In addition, the high signal detected by DWIBS decreases as inflammation improves, which is considered an indicator of inflammatory activity [ 10 , 19 ]. Given the lack of reported cases regarding the use of DWIBS for diagnosing isolated myocardial abscesses, it is imperative to explore the sensitivity and specificity of this diagnostic modality in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Given the lack of reported cases regarding the use of DWIBS for diagnosing isolated myocardial abscesses, it is imperative to explore the sensitivity and specificity of this diagnostic modality in future studies. Previous research has reported that the sensitivity of abdominal ultrasound and DWIBS in diagnosing acute cholecystitis to range from 37.5 to 91%, and 90.9% respectively [ 19 ]. In the present case, contrast-enhanced CT was used to monitor the abscess due to normal renal function and lower imaging frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous transhepatic gallbladder drainage (PTGBD), which was first applied by Radder in 1980 [ 11 ], is a minimally invasive operation performed to relieve gallbladder tension through external drainage under ultrasound or CT guidance [ 3 ]. According to the 2018 Tokyo guidelines for drainage management of AC, PTGBD can alleviate inflammation caused by edema of the gallbladder wall and pericholecystic adhesions, and it has the advantage of a lower risk of adverse events compared with cholecystectomy, which is an alternative to surgical treatment in high-risk AC patients [ 6 , 12 , 13 ]. Previous studies have reported that LC performed after PTGBD has several advantages, such as early symptom remission, surgery facilitation and patient stabilization [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%